Rice production in Chitwan district of Nepal: An analysis from economic and environmental perspectives (Journal of Agriculture and Natural Resources, 2021)
Rice (Oryza sativa L.) is the major staple food in the Nepalese context. Chitwan district of Nepal was purposively selected to analyze the rice production from the socio-economic and environmental perspective. A total of 100 rice growing farmers, 50 organic and 50 inorganic were selected as the sample for the purpose of the study using the simple random method of sampling. Primary data were collected through a pre-tested semi-structure interview schedule and key informant interviews; secondary data were collected reviewing related publications. Descriptive statistics, multiple regression and chi-square test were used for data analysis. The multiple regression revealed that the four explanatory variables included in the model: age of the household head, primary occupation of the household head, number of family members involved in agriculture and subsidy in inputs for rice farming were found to have positive and statistically significant effect on rice yield (P